EXPOSURE TO HYDROGEN SULPHIDE AMONGST SEWAGE WORKERS IN A METROPOLITAN MUNICIPALITY IN GAUTENG PROVINCE, SOUTH AFRICA (Proceedings of the International Conference on Public Health, 2026)
The study’s objectives were to determine concentration levels of hydrogen sulphide (H2S) in the working environment and its effects by describing the self-reported health effects and hydrogen sulphide among municipal sewage workers in the City of Johannesburg metropolitan municipality within Gauteng Province. One hundred and fifty- six participants from six different municipal wastewater treatment works were sampled. To determine any relation between self-reported outcomes and hydrogen sulphide exposure, a structured self-administered questionnaire was used. During an eight-hour shift, Drager X- am 5000 gas detectors were used to measure the concentration levels of hydrogen sulphide in the ambient air within three distances from operational sections. Concentration levels of hydrogen sulphide in the ambient air ranged from 0.99 ppm (parts per million) to 39.97 ppm, with a standard deviation (SD) of 8.72 and a mean of 12.83 ppm at a 5-meter distance, in effect the exposure levels were above the international and South African recommended exposure limit for an eight-hour shift. The self-reported health outcomes revealed that 33% of participants suffered from eye irritation, while 35% suffered from tiredness. The results also indicated that 33% of participants experienced headaches. Experiencing a burning sensation in the chest is positively correlated with hydrogen sulphide levels within 10 meters and 15 meters, according to the bivariate analysis. The results provide evidence of a correlation between self-reported outcomes and hydrogen sulphide exposure. The study also highlights that concentration levels of hydrogen sulphide closer to the source are much higher. Despite the current local and international legislation, workers continue to be exposed to higher levels of this harmful gas, thus highlighting the need for interventions.
Keywords: Hydrogen sulphide concentration levels; health outcomes; hydrogen sulphide exposure; risk factors and wastewater treatment works workers